Stripped: contribution of cyanobacterial extracellular polymeric substances to the adsorption of rare earth elements from aqueous solutions - Paper, Michael; Jung, Patrick; Koch, Max; Lakatos, Michael; Nilges, Tom; Brück, Thomas B. (Frontiers in Bioengineering and Biotechnology, 2023)
The transformation of modern industries towards enhanced sustainability is facilitated by green technologies that rely extensively on rare earth elements (REEs) such as cerium (Ce), neodymium (Nd), terbium (Tb), and lanthanum (La). The occurrence of productive mining sites, e.g., is limited, and production is often costly and environmentally harmful. As a consequence of increased utilization, REEs enter our ecosystem as industrial process water or wastewater and become highly diluted. Once diluted, they can hardly be recovered by conventional techniques, but using cyanobacterial biomass in a biosorption-based process is a promising eco-friendly approach. Cyanobacteria can produce extracellular polymeric substances (EPS) that show high affinity to metal cations. However, the adsorption of REEs by EPS has not been part of extensive research. Thus, we evaluated the role of EPS in the biosorption of Ce, Nd, Tb, and La for three terrestrial, heterocystous cyanobacterial strains. We cultivated them under N-limited and non-limited conditions and extracted their EPS for compositional analyses. Subsequently, we investigated the metal uptake of a) the extracted EPS, b) the biomass extracted from EPS, and c) the intact biomass with EPS by comparing the amount of sorbed REEs. Maximum adsorption capacities for the tested REEs of extracted EPS were 123.9–138.2 mg g−1 for Komarekiella sp. 89.12, 133.1–137.4 mg g−1 for Desmonostoc muscorum 90.03, and 103.5–129.3 mg g−1 for Nostoc sp. 20.02. A comparison of extracted biomass with intact biomass showed that 16% (Komarekiella sp. 89.12), 28% (Desmonostoc muscorum 90.03), and 41% (Nostoc sp. 20.02) of REE adsorption was due to the biosorption of the extracellular EPS. The glucose- rich EPS (15%–43% relative concentration) of all three strains grown under nitrogen-limited conditions showed significantly higher biosorption rates for all REEs. We also found a significantly higher maximum adsorption capacity of all REEs for the extracted EPS compared to cells without EPS and untreated biomass, highlighting the important role of the EPS as a binding site for REEs in the biosorption process. EPS from cyanobacteria could thus be used as efficient biosorbents in future applications for REE recycling, e.g., industrial process water and wastewater streams.